Initial Psychometric Evidence of Physical Inactivity Perceived Experience Scale (Pipes): COVID-19 Pandemic as a Pilot Study - Guelmami, Noomen; Chalghaf, Nasr; Tannoubi, Amayra; Puce, Luca; Azaiez, Fairouz; Bragazzi, Nicola Luigi (Frontiers in Public Health, 2022)
Aims: Our study aimed to develop a two-factor self-administered orthogonal questionnaire to assess the experience of perceived physical inactivity, to test its psychometric properties, to confirm its relationships with fear of COVID-19, and finally, with perceived stress during the pandemic.Methods: A total of 481 Tunisian subjects collected in several cities, aged from 16 to 67 years with a mean age = 32.48 ± 9.46, and of both sexes participate in our study with (male: 51.8%) and (female: 48.2%), divided according to the level of study into three categories. All subjects voluntarily answered the PIPES questionnaire, the IPAQ scale, the COVID-19 fear scale and the PSS-10 test. Results: The results of the exploratory and confirmatory factor analysis supported the robustness of the tool measure. In addition, examination of configurational, metric, scalar, and strict invariance supported the equivalence of the structure by gender and educational level. Concurrent validity was established by the positive association of a negative perception of physical inactivity with scores measured by the IPAQ scale and a negative association with scores of COVID-19 fear and perceived stress. Whereas, a positive perception of physical inactivity from the COVID-19 scale was negatively associated with the IPAQ and positively associated with fear of COVID-19 and perceived stress. However, no strong relationship was found between coping strategies among the two components of the PIPES-10 scale. Conclusion: The PIPES-10 scale can be used to measure the perception of physical inactivity in different situations.